POKOK-POKOK MATERI PENDIDIKAN KARAKTER BERBASIS FOLKLOR BALI - I Putu Suardipa (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
This research article aims to analyze the main points of Balinese folklore-based character education materials in learning Hinduism in elementary school. This research uses a qualitative research approach, with descriptive methods. The research sample consisted of elementary school teachers who taught Hinduism in classes I, II, and III, which were spread across Bali Province. Research data were collected using a questionnaire. Data were analyzed using descriptive qualitative analysis techniques with a percentage. The results of the study aimed to find out the types of Balinese Folklore that are used in learning Hinduism in grades I, II and III of Primary Schools in the Province of Bali. So that in mapping learning the effectiveness of learning meaningful absolutely will be obtained.Key Word: Basic material analysis, character education, Balinese folklore